Arthropod bioindicators of environmental quality - Márcia Soares Spiller; Claiton Spiller; Juliana Garlet (Agro@mbiente On-line)
The phylum Arthropoda is one of the most diverse groups under the terrestrial surface comprising different classes of insects that occupy different environments. Some groups have a close relationship with the habitat they occupy, responding significantly to changes in the environment, thus indicating the level of change in the environment by their presence or absence. The present study aimed to demonstrate the importance of edaphic fauna as a bioindicator of environmental quality. This is a bibliographic review based on specialized consultation of scientific articles in the databases Google Scholar, SciELO-Scientific Electronic Library and ResearchGate. The studies found that environmental quality can be measured from the diversity and abundance of arthropods that live and perform their functions in the soil. Macrofauna influences important soil chemical and physical processes such as nutrient cycling, structuring and homogenization, and increased productivity, among others. The mesofauna, besides acting on soil properties, acts on the regulation of microbial populations, is sensitive to changes and responds promptly. The groups Acari, Collembola, Coleoptera, Hymenoptera and Araneae are indicated in several studies as potential bioindicators because they are commonly sampled in different environments. The factors identified as conditioning factors of the presence of these groups are environmental heterogeneity, type of vegetation cover and availability of litter, applied management system, seasonality, soil characteristics, and anthropic activities, among others. In short, because they respond quickly, the changes are considered to be efficient biological indicators; therefore, knowing the diversity of species and their degree of interaction with the environment allows us to analyze the effects of anthropic modifications in ecosystems.